Crescimento de cultivares de salsa (Petroselinum crispum) em condições de sombreamento e a pleno sol - Hoepers, Lívia Maria Lemos (2017)
Parsley is a culture known in Brazil and in countries around the world as a condiment used in cooking both fresh and dehydrated. Because it is a culture from the Mediterranean region, the parsley presents difficulties in its development in regions of hot weather, or times with high temperatures in producing regions. It is sought in agriculture to improve the performance of plants grown under adverse conditions, thus increasing their productivity and yield relative to their final destination in trade. In the horticulture, one of the practices used is the use of cover to reduce the direct solar radiation on the canopy of the plants, and, thus, to reduce the temperature in that environment, improving the environmental conditions for the growth of the plants. In this way, the objective of this work was to evaluate the growth of plants of two varieties of parsley cultivated under two conditions of shade and at full sun in the spring, autumn and winter periods. The experiments were conducted in the period from October 2015 to December 2015 (spring), March to May 2016 (autumn) and June to August 2016 (winter), in a randomized block design in a split plot scheme with Analysis of environments. The treatments consisted of two cultivars (Graúda Portuguesa and Lisa Comum) and two types of shading (black screen and thermo-reflective screen, both at 50%) and full sun. Six analyzes were performed after transplanting, with a ten-day interval between them, in order to obtain the behavior of the plant growth curves. The plants were evaluated in relation to plant height, dry shoot mass, leaf dry mass, leaf area, leaf area ratio, absolute and relative growth rates and net assimilation rate, as well as productivity. It was verified that the plants cultivated under black screen, in the spring season, presented larger leaf area, which was caused by shading. The dry mass of the plants in this condition were the lowest in relation to the other tested environments. This proves the interference of shading in cultivation during the spring. There was a significant difference between the cultivars, being that Lisa Common was outstanding in the crops in all the times tested. The highest values of average productivity were reached by the plants cultivated in the winter, standing out the plants grown in full sun. If the objective of the production is the commercialization of the plants in natura, the best option of cultivation, in the winter period, is the full sun. In the spring and autumn periods, the use of the black screen is efficient in the production of plants with higher fresh shoot mass.